1993
DOI: 10.1002/tox.2530080407
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of microcystis species and toxic heptapeptide microcystins in lake suwa

Abstract: Seasonal changes in species composition of Microcystis and concentrations of toxic heptapeptide microcystins, were investigated in Lake Suwa from June to October in 1991. Microcystins-RR and -LR were the main components of the toxins contained in bloom samples of Microcystis and a very little quantity of -YR was detected through this period. The high amounts of microcystins were estimated during the exponential growth phase of the bloom from June 11 to July 20. The highest concentrations of microcystins-RR and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 15 publications
7
45
1
Order By: Relevance
“…1, the cyanobacterial biomass was considerably reduced comparing with the other three sites. We detected strange phenomenon that frequent variations of toxin species and toxin concentrations in bloom samples from the same sampling site, even within short-term period, which could be also observed in previous studies (Watanabe et al, 1992;Park et al, 1993;Vezie et al, 1997). However, laboratory culture experiments performed to investigate the relationship between toxin production and cultural conditions in unicellular or colony Microcystis (Utkilen and Gjolme, 1995;Lehtimä ki et al, 1997) do not explain why these frequent and substantial variations occur for either toxin concentrations or toxin species in the natural aquatic environment.…”
Section: Environmental Fatesupporting
confidence: 88%
See 1 more Smart Citation
“…1, the cyanobacterial biomass was considerably reduced comparing with the other three sites. We detected strange phenomenon that frequent variations of toxin species and toxin concentrations in bloom samples from the same sampling site, even within short-term period, which could be also observed in previous studies (Watanabe et al, 1992;Park et al, 1993;Vezie et al, 1997). However, laboratory culture experiments performed to investigate the relationship between toxin production and cultural conditions in unicellular or colony Microcystis (Utkilen and Gjolme, 1995;Lehtimä ki et al, 1997) do not explain why these frequent and substantial variations occur for either toxin concentrations or toxin species in the natural aquatic environment.…”
Section: Environmental Fatesupporting
confidence: 88%
“…However, these cell-bound toxins are eventually released into the surrounding water body by senescence of the blooms which leads to the creation of dissolved MCs in the water column (Park et al, 1993;Sivonen and Jones, 1999). To assess the health implications of exposure, it is crucial to pursue MCs under field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, only the largest colonies of Microcystis (Ͼ100 m) were sampled individually in the study of Kurmayer et al (14), and it has also been found that the larger colonies (Ͼ340 m) had the highest mcyB proportion but contributed the smallest fraction to the total cell number, Ͻ10% (15). On the other hand, Microcystis populations have been found to vary in hepatotoxicity within a few weeks, e.g., in 50% lethal dose (expressed in milligrams [dry weight] per kilogram of body weight) (7) or in microcystin concentration (12,21), and a mosaic structure for toxic cyanobacterial blooms has been suggested (4,22,30). In the present study, with one exception, short-term variation ranged from 1 to 38%, and the data on mcyB genotype proportions showed maxima on a weekly or biweekly scale (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, microcystins are usually present inside cyanobacterial cells during the growth and steady phase of blooms (Rapala et al, 1997;Sivonen et al, 1990). But, these cell-bound toxins are eventually released into the surrounding water body by senescence of the blooms (Park et al, 1993;Sivonen and Jones, 1999). Therefore, some sequences are closely affiliated with Sphingomonas that were found following Microcystis decomposition in our study.…”
Section: Phylogenetic Analysis Of the Particle-attached Bacterial Commentioning
confidence: 99%
“…Some studies showed that dense blooms can deplete oxygen through decomposition (de Figueiredo et al, 2006), and lysis of Microcystis cells significantly influences the nutrient status of the surrounding water (Ye et al, 2010). Additionally, Microcystis can produce large quantities of microcystins, released into the surrounding water body by senescence of the blooms (Park et al, 1993;Sivonen and Jones, 1999). However, the changes in these environmental conditions induced by decomposition of Microcystis blooms may also influence population dynamics of the attached bacteria in the water column, which has rarely been studied in freshwater ecosystems.…”
Section: Introductionmentioning
confidence: 99%